Konceptualizacja porównaniowa. Próba typologii - Kudra, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The author treated the comparison as a basic cognitive-axiological figure. He distinguished classical comparisons with the functor and conceptual comparisons without the functor. The author analyzed the comparisons with the functor and distinguished following types of the comparative conceptualisation: attributive, imitative, metaphysical, time-spacious, concrete, abstract.